Genetic variability, correlation and path coefficient analysis of exotic white maize (Zea mays L.) genoytpes: Variability and trait association in white maize - Roy, G; Shompa, BN; Emu, I A; Fatima , K; Rahman, J (Bangladesh Journal of Agriculture, 2026)
Seventeen exotic white maize (Zea mays L.) inbred lines collected from CIMMYT, Mexico were evaluated at the experimental farm of Sher-e-Bangla Agricultural University, Dhaka in a Randomized Complete Block Design (RCBD) with three replications, during October 2016 to April 2017. The mean performance, variability, correlation matrix and path analysis on different yield parameters and yield were estimated. Maximum grain yield plant-1 (170.01 g) was recorded in the genotype, CLTHW15008, whereas the minimum grain yield plant-1 (44.52 g) was recorded in CLTHW15007.The phenotypic co-efficient of variation was higher than the genotypic co-efficient of variation for all the yield contributing traits. In the correlation study, a significant positive association was recorded for grain yield with the base diameter of the plant (1.00), leaf breadth (1.00), cob length (0.979), cob diameter (0.930), number of rows cob-1 (0.979), number of grains row-1 (0.999), 100-grain weight (0.992). Path analysis revealed that plant height (0.412), leaf breadth (0.073), days to 50% flowering (0.280), number of rows cob-1 (0.462), number of grains row-1 (0.209) had a positive direct effect on yieldplant-1. The results indicated that for improving white maize grain yield, selection based on plant height, cob length, cob diameter, number of rows cob-1,number of grains row-1, 100-grain weight would be useful for future breeding program. Bangladesh J. Agri. 2025, 50(2): 132-146